2008
DOI: 10.1007/s11999-008-0198-3
|View full text |Cite
|
Sign up to set email alerts
|

Increased Oxacillin Resistance in Thigh Pyomyositis in Diabetic Patients

Abstract: Thigh abscesses due to pyomyositis are uncommon. To guide empiric antibiotic therapy in diabetics we determined the rate of such infections due to oxacillin-resistant Staphylococcus aureus and Gram-negative organism infections, and whether the occurrence of oxacillin-resistant pathogens increased during the study period. We retrospectively reviewed 39 adult patients with diabetes mellitus treated for a deep thigh abscess. There were 29 men and 10 women; their mean age was 45 years. Comorbidities were present i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
2

Year Published

2010
2010
2025
2025

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 29 publications
1
13
0
2
Order By: Relevance
“…Classically, it is an infection of the tropics, occurring in previously active and healthy young men. 9 Pyomyositis in temperate countries is often regarded as an infection that occurs in hosts who are immune compromised or otherwise debilitated.…”
Section: Introductionmentioning
confidence: 99%
“…Classically, it is an infection of the tropics, occurring in previously active and healthy young men. 9 Pyomyositis in temperate countries is often regarded as an infection that occurs in hosts who are immune compromised or otherwise debilitated.…”
Section: Introductionmentioning
confidence: 99%
“…Timing of presentation and the clinical stage affects the imaging findings but early MRI is invaluable even in the absence of a collection 12. Early identification of the pathogen is crucial to guide in antibiotic choice as there is an increasing incidence of methicillin-resistant S aureus being isolated from infected individuals13 14 only a small minority of which may have favourable outcomes 15…”
Section: Discussionmentioning
confidence: 99%
“…Most of them are superficial and are readily treated with local care and oral antibiotics. However, they may affect deeper structures including fascia and muscle 16 . Charalambous et al 86 reported on 142 consecutive hospital admissions to treat acute soft-tissue infections of the extremities between 1996 and 2001; half of the infections were cellulitis and a substantial proportion (fortythree) were abscesses.…”
Section: Non-necrotizing Soft-tissue Infections: the Additional Finanmentioning
confidence: 99%
“…Soft-tissue infections such as cellulitis, abscesses, and pyomyositis from community-acquired methicillinresistant Staphylococcus aureus occur with increasing frequency in athletes, especially in those engaged in team sports [14][15][16] . Health-care-acquired methicillin-resistant Staphylococcus aureus generally affects acutely and chronically ill patients with central lines, indwelling catheters, and internal fixation devices, causing septic arthritis, osteomyelitis, and bacteremia 17 .…”
mentioning
confidence: 99%